Pregnancy immune tolerance at the maternal-fetal interface. (1st November 2020) - Li, Xiaopeng; Zhou, Jiayi; Fang, Min; Yu, Bolan
Abstract: Pregnancy is a natural process that poses an immunological challenge because non-self fetus must be accepted. During the pregnancy period, the fetus as 'allograft' inherits maternal and also paternal antigens. For successful and term pregnancy, the fetus is tolerated and nurtured enjoying immune privileges that minimize the risk of being rejected by maternal immune system. Multiple mechanisms contribute to tolerate the semi-allogeneic fetus. Here, we summarize the recent progresses on how the maternal immune system actively collaborates to maintain the immune balance and maternal-fetal tolerance.